The effect of harm-free pharmacotherapy training program on awareness and performance of type 2 diabetic patients - Afsaneh Mosleh; Najmolmolook Amini; Masoume Sehati; Maryam Soroush (Payesh)
Objective(s): There is a possibility of serious harm to the patient with misuse of drugs, so it is important to pay attention to the safety of drug use. In this study, the effect of non-harm drug therapy education on the level of knowledge and performance of type 2 diabetic patients in primary health care programs was evaluated. Methods: This was an experimental study covering urban and rural health centers in Tehran. Health center were randomly selected and the number of samples were determined based on the population density covered by the centers. The sample size was estimated to be 496, and the selection of intervention and control samples in each pharmacy was done randomly when the patient visited. The measurement tool in this research was a self-designed questionnaire including 2 areas of drug therapy without injury, and 5 structures (1-starting drug use, 2-taking own drug, 3-adding another drug, 4-reviewing own drugs, 5-discontinuing drug use).and the educational intervention included face-to-face training and delivery of pamphlets. Results: The data for 496 patients (277 the intervention group and 219 the control group) were assessed. In terms of demographic information, except for educational qualification (P = 0.046), there was no significant difference between the intervention and the control group. Comparison of the average score of awareness after the intervention between the study groups was significant (p=0.001). Also the comparison of the average performance score before and after the intervention in the test group (p < 0.001) was significant. Conclusion: Education of drug therapy for patients with type 2 diabetes at primary health centers increases the awareness and performance of patients.